The Safety of Medicinal Plants Used in the Treatment of Vitiligo and Hypermelanosis: A Systematic Review of Use and Reports of Harm - Hussain I (Dove Medical Press, 2021)
Irshad Hussain Institute of Pharmacy, Shaheed Mohtarma Benazir Bhutto (SMBB) Medical University, Larkana, PakistanCorrespondence: Irshad HussainInstitute of Pharmacy, Shaheed Mohtarma Benazir Bhutto (SMBB) Medical University, 7 Doctors Colony, Along VIP Road, Larkana, 77150, Sindh, PakistanTel +92 31 27214112Email irshadpharmacist@yahoo.comIntroduction: Vitiligo is disfiguring and devastating condition that can humans feel stigmatic and devalued. Melasma is a general condition of hyperpigmentation particularly involving the face. The pigmentation disorders of vitiligo (hypopigmentation or de-pigmentation) and melasma (Hypermelanosis) are common among the world’s population (around 1% for vitiligo).Objective: The identification of medicinal plants used in the treatment of vitiligo and hypermelanosis. A systematic literature review on harms associated with the medicinal plants used in the treatment of vitiligo and hypermelanosis. To review and summarize information on reported adverse drug reactions (ADRs) associated with these medicinal plants contained in (where access is available) national and global individual case safety report databases.Methods: A systematic review of the literature with special reference to all types of clinical trial and case reports using biomedical databases including Medline, EMBASE, Scopus, International Pharmaceutical Abstracts and so forth to identify medicinal plants alone or as an adjuvant with other treatments and their safety/tolerability in the treatment of vitiligo and Hypermelanosis. Other sources of this search were medicinal plants text books, pharmacopoeias and authentic websites discussing possible treatments for vitiligo/hypermelanosis. It also included databases such as VigiAccess containing data from spontaneous reporting schemes for ADRs.Results: A total of 55 articles (47 clinical trials and 8 case reports) met the inclusion criteria. Some trials did not reported safety information, some did report, but not very well. Reports of blistering, erythema, acute hepatitis and mutagenesis with Psoralea corylifolia. Adverse effects of erythema (mild to severe), phototoxic reactions, mild raise in liver transaminases, gastrointestinal disturbances, burns, itching, scaling, depigmented macules, pruritis, and giddiness with the use of psoralens. Khellin-related erythema, perilesional hyperpigmentation, gastrointestinal disturbances, mild raise in liver transaminases and orthostatic complaints. Infrequent side effects with Ginkgo biloba. Lower grade of erythema and edema reported with the use of Polypodium leucotomos.Conclusion: Primarily the retrieved clinical studies were efficacy oriented and safety parameters were secondary in priority whilst the general protocol of clinical trials requires the screening of drugs/medicinal plants on the basis of safety studies before testing the clinical aspects of efficacy. Thereby it is recommended that efficacy studies may be followed once the safety has been established for a particular medicinal plant in treating vitiligo and hypermelanosis.Keywords: vitiligo, hypermelanosis, skin diseases, safety of medicinal plants, harm of herbs